The Effects of Information Level on Human-Agent Interaction for Route Planning. (September 2015) - Wright, Julia L.; Chen, Jessie Y.C.; Barnes, Michael J.; Boyce, Michael W.
Two experiments were conducted to examine the effects of level of information on human operators' route selection decisions. Experiment 1 examined how information about resource usage/requirements affected route selection decisions for a remotely based supervisor guiding a dismounted soldier unit through an urban environment. Experiment 2 increased the level of information from Experiment 1 by adding a robotic asset to the unit and providing its resource usage/requirements. Decision time increased as the level of information increased and increased again with the addition of the robotic asset. In addition, as the level of information increased, preference for specific information sources began to vary. In the condition with the greatest level of information available, participants displayed no clear consensus as to preferred information source, with many indicating they relied upon sources that were unsuitable for successful mission completion. Future research could investigate further into the complexity of appropriate display for user interfaces involving robotic assets.